Leverage and Profitability on Company Dividend Policy in Moderation of Audit Committee and Gender Diversity - Sandra Yunita Hidayat; Iwan Kusumayadi (LP2M IAIN Palopo, 2026)
This study examines the effect of leverage and profitability on dividend policy moderated by audit committees and gender diversity in non-financial companies in Indonesia, where previous empirical findings have been inconsistent due to differences in financial theory and the emerging market context. The study aims to examine the direct effect of leverage and profitability on the Dividend Payout Ratio (DPR) and the moderating role of governance mechanisms. Using a quantitative explanatory approach with panel data regression Fixed Effect Model on the population of non-financial companies listed on the Indonesian Stock Exchange (IDX) for the period 2019-2023, a purposive sample of 78 companies (390 observations) was used. Secondary data instruments from financial statements were analyzed through descriptive analysis, the Chow-Hausman test, classical assumptions, multiple regression, and Moderated Regression Analysis (MRA) with EViews 13. The results show that leverage and profitability have no significant partial effect (p>0.05), while audit committees and gender diversity do not moderate the relationship, although the simultaneous model is significant (F-statistic p=0.000). The conclusion states that dividend policy is more determined by managerial factors than financial ratios or formal governance, so investors need to consider the company's internal strategy